2018
DOI: 10.1213/ane.0000000000003413
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Pharmacodynamics of Dexmedetomidine in Children Undergoing Ambulatory Surgery

Abstract: BACKGROUND:Dexmedetomidine (DEX) is an α-2 adrenergic agonist with sedative and analgesic properties. Although not approved for pediatric use by the Food and Drug Administration, DEX is increasingly used in pediatric anesthesia and critical care. However, very limited information is available regarding the pharmacokinetics of DEX in children. The aim of this study was to investigate DEX pharmacokinetics and pharmacodynamics (PK–PD) in Mexican children 2–18 years of age who were undergoing outpatient surgical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 33 publications
3
40
0
1
Order By: Relevance
“…A maximum mean arterial blood pressure reduction of 45% was predicted with an inhibitory concentration IC50 of 0.501 ng/mL, and a maximum heart rate reduction of 28.9% with an IC50 of 0.552 ng/mL. Clearance was lower in the pediatric population [10]. This predictability of serum concentrations of DEX to elicit a particular hemodynamic response (reduced heart rate and the biphasic effect on mean arterial pressure) is consistent with the adult literature.…”
Section: Updates On Pharmacologysupporting
confidence: 84%
“…A maximum mean arterial blood pressure reduction of 45% was predicted with an inhibitory concentration IC50 of 0.501 ng/mL, and a maximum heart rate reduction of 28.9% with an IC50 of 0.552 ng/mL. Clearance was lower in the pediatric population [10]. This predictability of serum concentrations of DEX to elicit a particular hemodynamic response (reduced heart rate and the biphasic effect on mean arterial pressure) is consistent with the adult literature.…”
Section: Updates On Pharmacologysupporting
confidence: 84%
“…It is metabolised by glucuronidation and CYP2A6 hydroxylation and subsequently excreted in urine almost exclusively as metabolite [2]. Its pharmacokinetics has been described by a two-compartmental model both in adults [3][4][5][6][7] and children [8][9][10][11][12]. Still, other investigators have also reported the disposition of dexmedetomidine according to one-compartment [13] and three-compartment [14][15][16] models.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that with the increasingly widespread use of DXM in the paediatric population and especially neonates and infants, cases of adverse effects may increase if the clinician does not have dosage recommendations based on PK-PD studies. Thus, having a precise and minimally invasive method for quantification of DXM can be an important contribution to enhance the efficacy and safety of this drug [11].…”
Section: Discussionmentioning
confidence: 99%
“…Currently there is a need for clinical and pharmacokinetic studies in paediatrics, which are useful to establish the optimal personalised dose; since the FDA has not approved it yet to be used in this population [10, 11]. In addition, other obstacles to perform such clinical trials have been the obtaining of the sample (venous puncture with catheter) and the amount of blood.…”
Section: Introductionmentioning
confidence: 99%